Effect of Lithium Ions on Copper Nanoparticle Size, Shape, and Distribution - Kyung-Deok Jang; Ada Ortega; Justin Ucol; Hao Du; Nam-Soo Kim (Journal of Nanotechnology)
Copper nanoparticles were synthesized using lithium ions to increase the aqueous electrical conductivity of the solution and precisely control the size, shape, and size distribution of the particles. In this study, the conventional approach of increasing particle size by the concentration of copper ions and PGPPE in a copper chloride solution was compared to increasing the concentration of lithium chloride when the copper chloride concentration was held constant. Particle size and shape were characterized by TEM, and the size distribution of the particles at different concentrations was obtained by particle size analysis. Increasing the concentration of copper ion in the solution greatly increased the aqueous electric conductivity and the size of the particles but led to a wide size distribution ranging from 150 nm to 400 nm and rough particle morphology. The addition of lithium ions increased the size of the particles, but maintains them in a range of 250 nm. In addition the particles exhibited spherical shape as determined by TEM. The addition of lithium ions to the solution has the potential to synthesize nanoparticles with optimal characteristics for printing applications by maintaining a narrow size range and spherical shape.